Entrepreneur’s Intrapersonal Resources and Enterprise Success among Micro and Small Scale Women Entrepreneurs - Katongole, Celestine; Munene, John C.; Ngoma, Muhammed; Dawa, Samuel (Journal of Enterprising Culture, 2015)
The study explores the relationship between intrapersonal resources (formal schooling, formal entrepreneurial education and training, and informal entrepreneurial training and education) and success of micro and small enterprises (MSEs). Using Structural Equation Modeling, the study tested the mediating role of entrepreneurial competence in this relationship on a sample of 303 women drawn from the tourism and hospitality sector. The results reveal that entrepreneurial competence plays a mediating role in the relationship between intrapersonal resources and enterprise success. The results also show that informal entrepreneurial training is important in complementing formal entrepreneurial training and education towards enterprise success. It is also shown that formal schooling has a weak relationship with entrepreneurial competence but has varying relationships with both financial and non-financial success.
Keywords: Women entrepreneurs; Micro and small enterprises; Entrepreneurial resources; Formal schooling; Formal entrepreneurial education